2009
DOI: 10.1111/j.1095-8649.2009.02328.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the timing of initial feeding on growth and survival of spotted mandarin fish Siniperca scherzeri larvae

Abstract: The effects of delayed first feeding on growth and survival of spotted mandarin fish Siniperca scherzeri larvae were examined under controlled conditions. Morphometric characters [yolk-sac volume, oil globule volume, head depth (H(D)), body depth (B(D)), eye diameter (E(D)), musculature height (M(H)), mouth diameter (M(D)) and total length (L(T))], body mass (M), specific growth rate (S(GR)) and survival were evaluated under different first-feeding time (2, 3, 4 and 5 days after hatching). Larvae began to feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 34 publications
3
22
0
1
Order By: Relevance
“…The results showed that larval growth of Chinese perch was sensitive to the timing of first feeding. Similar results have also been found in spotted mandarin fish Siniperca scherzeri, which is also piscivorous at the time first feeding (Zhang et al 2009). In contrast, larvae of most fish species that are not piscivorous at first feeding time, such as Malabar grouper Epinephelus malabaricus (Yoseda et al 2006) and Asian sea bass (Kailasam et al 2007), do not show any difference in growth when fed before or at the time of complete yolk absorption.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The results showed that larval growth of Chinese perch was sensitive to the timing of first feeding. Similar results have also been found in spotted mandarin fish Siniperca scherzeri, which is also piscivorous at the time first feeding (Zhang et al 2009). In contrast, larvae of most fish species that are not piscivorous at first feeding time, such as Malabar grouper Epinephelus malabaricus (Yoseda et al 2006) and Asian sea bass (Kailasam et al 2007), do not show any difference in growth when fed before or at the time of complete yolk absorption.…”
Section: Discussionsupporting
confidence: 79%
“…The larvae of Chinese perch, similar to spotted mandarin fish Siniperca scherzeri larvae (Zhang et al 2009) and Japanese Spanish mackerel Scomberomorus niphonius larvae (Shoji et al 2002), only feed on live fish larvae at the time of first feeding (Chiang 1959;Liang et al 2008). Piscine prey is more evasive than plankton prey in general and requires higher foraging ability of the predator (Shoji and Tanaka 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, numerous studies on the propagation, farming, and nutrition of S. scherzeri have been reported (Zhao et al, 2009;Zhang et al, 2009;Tu et al, 2011), while few studies have focused on genetic variability and the population structure of reared populations. In this study, by using microsatellite markers, we estimated the genetic variation in 5 generations of a selected breeding line of golden mandarin fish, which has been established through collaboration between the Key Lab of Freshwater Animal Breeding, Ministry of Agriculture, and the Jing-Bo Hatchery in Dandong, Liaoning Province.…”
Section: Introductionmentioning
confidence: 99%
“…The Chinese mandarin fish (CMF) is the most important aquaculture species in China as well as in Eastern Asia [12]. CMF includes seven subspecies, but only two of them, S. chuatsi, and S. scherzeri, have become widely aquaculture species.…”
Section: Introductionmentioning
confidence: 99%